THE IMPACT OF MIGRATION ON THE WAGE DISTRIBUTION IN INDONESIA - Pravitasari, Clalisca (AFEBI Economic and Finance Review, 2018)
Research on the impact of migration on workers' wages in destination areas has long been debated in the literature. However, studies that link migration to wage rates in different percentiles along the distribution have not been widely implemented, as migration does not have the same impact on wage levels in all groups of workers. By establishing a counterfactual using the semi-parametric DFL method of National Labor Force Survey data, this study found that migration promotes changes in the distribution of wages, especially in the upper and lower percentiles. After controlling the magnitude of in-migration in each percentile group by using the ordinary least square method, this study also proves that migration leads to wage decreasing in percentile groups where migrant workers are overrepresented, which is in the 75th and 90th percentile groups. Meanwhile, no negative impacts were found on wage levels in the lower middle percentile. In fact, migration has proven to encourage an increase in the average wage of workers in the lowest percentile of the distribution. JEL Classification: J01, J11, J61 Keywords: counterfactual, migration, wage distribution